Extragenital endometriosis associated with uterine scar defects - Tilman Born; Katrin Krejci; Maximilian Rauh; Georgia Cole; Maurice Kappelmeyer; Mehmet Vural; Angela Köninger (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Introduction: Uterine scar defects result from poor healing of the hysterotomy after cesarean sections (CS), in multiple cases leading to retroflexio uteri and retrograde menstruation. Endometriosis is the probable consequence. Patients often experience overlapping symptoms such as dysmenorrhea, dyspareunia, and infertility. Material and methods: This study analysed cases of sonographically detected uterine scar defects, subsequently undergoing laparoscopy at the University Clinic St. Hedwig, in Regensburg, between 2020 and 2024. Herefore, surgery reports were reviewed, focusing on extragenital endometriosis, symptoms of Cesarean Scar Disorder (CSD), niche morphology, uterine position, and endometriosis localisation using the #Enzian classification. Results: Extragenital endometriosis was histologically confirmed in 45 of 94 patients (47.9 %) with symptomatic or large uterine niches. A significant association was found between endometriosis and heavy menstrual bleeding (HMB) (p < 0.001) as well as retroflexio uteri (p = 0.036). Symptoms related to CSD did not differ in patients with or without Endometriosis. Endometriotic implants were primarily located in the peritoneum behind the uterus and sacrouterine ligaments, supporting the hypothesis of retrograde menstruation. Conclusion: There is significant overlap between the symptoms of endometriosis and CSD. Almost half of the patients with a symptomatic niche were found to have endometriosis, whereby the location of endometriosis supports the hypothesis of retrograde menstruation. However, the patient´s history of complaints is not indicative of the diagnosis of endometriosis. Therefore, all patients with CSD should be offered a laparoscopy and endometriosis surgery. All patients with a previous caesarean section presenting with symptoms of endometriosis should be offered standardised and high-quality niche diagnosis and treatment.